Packaging : design successful packaging for specific customer groups. - Hampshire, Mark, ....-; Stephenson, Keith, ....- (Mies : Rotovision, 2007)
The first book to explore the vital, commercial relationship between design, marketing, and the target audience. DemoGraphics is the first series of design books to examine how successful designs target specific audiences. Where other design books explore the 'what?' and 'why?' of design, DemoGraphics: Packaging dissects the 'who?' Through a huge selection of diverse examples, the authors examine how packaging is designed to appeal to specific groups based on gender, age, socio-economic group, disposable income, profession, and shopping habits. Case studies and interviews with designers and brand owners explain how and why specific choices have been made, why it works, and how it evolved from a prototype or concept to form a successful, user-centered design. Explores designs that work for target groups, together with case-study evidence, color wheels, materials and typeface choices. Unique mix of theory, showcase designs, research, statistics, and hard evidence. Loaded with hundreds of illustrations and featuring a hardcover format with tabbed dividers.
Keywords: Verpakkingen